2017
DOI: 10.1186/s13613-017-0251-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of cardiac surgery-associated acute kidney injury: differential roles of creatinine, chitinase 3-like protein 1 and neutrophil gelatinase-associated lipocalin: a prospective cohort study

Abstract: BackgroundA common and serious complication of cardiac surgery prompting early detection and intervention is cardiac surgery-associated acute kidney injury (CSA-AKI). Urinary chitinase 3-like protein 1 (UCHI3L1) was found to predict AKI associated with critical illness in adults. Our aims were therefore to evaluate whether UCHI3L1 can also be used to predict AKI associated with elective cardiac surgery in adults, and to compare this predictive ability with that of urinary neutrophil gelatinase-associated lipoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
2
22
1
1
Order By: Relevance
“…In a subsequent study, the group reported the association of urinary CHI3L1 to the development of AKI after cardiac surgery involving 211 patients. However, in this study urinary CHI3L1 was not predictive of AKI . The biological roles of CHI3L1 have been for a long time particularly enigmatic, but data has shown that intrarenal macrophage CHI3L1 plays a key role in promoting tubular cell survival after renal I/R injury in mice via PI3K‐ and IL‐13 receptor α2‐dependent signaling .…”
Section: Use Of Preclinical Model Kidney Proteome Analysis In Biomarkcontrasting
confidence: 60%
“…In a subsequent study, the group reported the association of urinary CHI3L1 to the development of AKI after cardiac surgery involving 211 patients. However, in this study urinary CHI3L1 was not predictive of AKI . The biological roles of CHI3L1 have been for a long time particularly enigmatic, but data has shown that intrarenal macrophage CHI3L1 plays a key role in promoting tubular cell survival after renal I/R injury in mice via PI3K‐ and IL‐13 receptor α2‐dependent signaling .…”
Section: Use Of Preclinical Model Kidney Proteome Analysis In Biomarkcontrasting
confidence: 60%
“…In this multicenter validation study, we found that uCHI3L1 was markedly increased in general ICU patients who developed AKI stage 2 or 3 within a 24-h [15]. This study and previous studies on uCHI3L1 have demonstrated its use as a biomarker for diagnosis of AKI, and this with comparable performance to uNGAL and NephroCheck Risk® [8,9,[17][18][19]. CHI3L1 may also provide mechanistic insights in injury and repair mechanisms in the kidney.…”
Section: Discussionmentioning
confidence: 52%
“…With the Astute140® Meter, we measured the concentrations of urinary TIMP-2, urinary IGFBP7, and NephroCheck Risk® by a fluorescent immunoassay technique (NephroCheck® Test, Astute Medical, San Diego, CA, USA). Details on these laboratory analyses were recently described [9].…”
Section: Laboratory Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the severity, AKI is classified into (1) severe (serum creatinine level increase >3 times of the initial value), requiring kidney replacement therapy, (2) moderate (serum creatinine level 2-3 times higher than the initial value), and (3) mild (serum creatinine level increases up to 1.5 times from the initial value) postoperative AKI. However, serum creatinine concentration is not an accurate and early indicator of the kidney condition, thus it is often suggested to use newer biomarkers instead, which allow earlier diagnosis and detect injuries of a minor degree (4). AKI can be diagnosed by serum level of neutrophil gelatinase-associated lipocalin (NGAL), which is a biomarker reflecting early kidney injury in the distal nephrons (5).…”
Section: Introductionmentioning
confidence: 99%